(untitled) (Theoretical and Applied Linguistics@ro, 2025)
In this study, we aim to examine the adverbial value of the adjective destul ‘enough’, given that – apart from a few brief investigations – the processes underlying its grammaticalization, its syntactic behaviour, and its combinatory potential from both a morphosyntactic and locutional perspective have not been sufficiently analysed for the period of Old Romanian. We begin by providing a series of etymological observations, after which our focus will shift to the enunciative functions fulfilled by destul ‘enough’, both in its role as a verbal or adverbial adjunct and as a degree modifier. The linguistic data under analysis are primarily approached from a diachronic perspective, though occasional references to contemporary Romanian are also made.